2016
DOI: 10.12659/msm.897451
|View full text |Cite
|
Sign up to set email alerts
|

The Low Expression of IL-37 Involved in Multiple Myeloma – Associated Angiogenesis

Abstract: BackgroundAngiogenesis plays a significant role in complex inflammatory and angiogenic processes and is also involved in multiple myeloma (MM) pathogenesis. IL-37 is a proinflammatory cytokine in antitumor activity. Our purpose was to evaluate the IL-37 clinical significance on MM.Material/MethodsWe measured serum levels of IL-37 in 45 patients with different stages of MM and 30 healthy control subjects and correlated IL-37 with numerous cytokines, such as angiogenesis factors including vascular endothelial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Li et al also reported that serum IL‐37 level had a negative correlation with VEGF and Ang‐2 levels. More interestingly, the tube formation of HUVECs was suppressed by rhIL‐37 pretreatment …”
Section: Mechanisms Involved In Il‐37 Antitumor Effects and Future Pementioning
confidence: 96%
See 3 more Smart Citations
“…Li et al also reported that serum IL‐37 level had a negative correlation with VEGF and Ang‐2 levels. More interestingly, the tube formation of HUVECs was suppressed by rhIL‐37 pretreatment …”
Section: Mechanisms Involved In Il‐37 Antitumor Effects and Future Pementioning
confidence: 96%
“…72,73 IL-37 expression was found to be lower in MM patients compared with healthy donors. 74 Moreover, IL-37 expression level is negatively associated with Ang-2 and VEGF levels. Ang-2 and VEGF are important angiogenesis factors during lymphatic and blood vessel formation.…”
Section: Multiple Myelomamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was also found that serum IL‐37 level had a negative correlation to VEGF and Ang‐2 levels. The tube formation of HUVECs was suppressed by the rhIL‐37 pretreatment . The biphasic pro‐angiogenic effect of IL‐37 might be due to its different expression level.…”
Section: The Role In Cardiovascular Diseasesmentioning
confidence: 97%